Exposed Rock Reduces Tree Size, but Not Diversity - Li, Jie; Zhang, Lianjin; Li, Yuanfa (Frontiers in Plant Science, 2022)
Karst made up of limestone, is widely considered a “Noah’s ark” of biodiversity. Rock and soil substrates comprise two different site types in karst terrain, although both can support dense forests. However, it is unclear whether and how the presence of exposed rock affects forest diversity and tree size. We established a 2.2 ha plot (200 m × 110 m) in an old-growth oak forest (> 300 years) in karst terrain in southwestern China. We classified the plot into rock and soil components; we analyzed plant diversity and tree size in each component using species diversity indices (richness, number of individuals, Shannon-Wiener index, and Pielou evenness index), stand spatial structure parameters, diameter at breast height (DBH), tree height (TH), and tree basal area (BA). We also analyzed the distributional patterns of species at the sites using nonmetric multidimensional scaling, then assessed the effects of abiotic environmental variables on diversity and tree size using redundancy analysis. Our results indicated that both site types (i.e., rock and soil) had similar overall species diversity; trees and shrubs were largely distributed at random within the study site. Tree size was evenly differentiated in the community, and trees were dominant, particularly on soil. Trees on rock were in a status of medium mixture, whereas shrubs on rock were highly mixed. The opposite trend was observed for trees and shrubs growing on soil. The DBH, TH, and BA were smaller in trees growing on rock than in trees growing on soil. Abiotic environmental variables had varying effects on the diversity and size of trees at the two site types; they only explained 21.76% and 14.30% of total variation, respectively. These results suggest that exposed rock has the effect of reducing tree size, but not diversity, thus highlighting the important role of rock in maintaining diversity; moreover, the results imply that karst microhabitats may mitigate the impacts of topography on tree diversity and growth. Greater attention should be focused on exposed rock in the conservation and management of karst forests and the restoration of degraded forest ecosystems.